In vivo and in vitro effects of chromium VI on anterior pituitary hormone release and cell viability - Quinteros, Alnilan Fernanda (2007)
Hexavalent chromium (Cr VI) is a highly toxic metal and an environmental pollutant. Different studies indicate that Cr VI exposure adversely affects reproductive functions. This metal has been shown to affect several tissues and organs but Cr VI effects on pituitary gland have not been reported. Anterior pituitary hormones are central for the body homeostasis and have a fundamental role in reproductive physiology. The aim of this study was to evaluate the effect of Cr VI at the pituitary level both in vivo and in vitro. We showed that Cr VI accumulates in the pituitary and hypothalamus, and decreases serum prolactin levels in vivo but observed no effects on LH levels. In anterior pituitary cells in culture, the effect of Cr VI on hormone secretion followed the same differential pattern. Besides, lactotrophs were more sensitive to the toxicity of the metal. As a result of oxidative stress generation, Cr VI induced apoptosis evidenced by nuclear fragmentation and caspase 3 activation. Our results indicate that the anterior pituitary gland can be a target of Cr VI toxicity in vivo and in vitro, thus producing a negative impact on the hypothalamic-pituitary-gonadal axis and affecting the normal endocrine function.